Impact of Industry Sector Index on Market Performance - Sunarto, Sunarto (AGUSPATI Research Institute, 2025)
This research aims to examine various sectors that are predicted to influence market returns. The research sample was obtained from the industrial sector index and LQ45 list for three LQ45 reporting periods from February 2022 – July 2023. Data was obtained based on calculations of sector returns and market returns from the sector index and LQ45 index totaling 321 observations. The analysis technique used is multiple linear regression with the help of SPSS version 24 software. The results of the analysis show that seven sectors have a significant positive effect on market performance; while one significant sector had a negative effect, and the other two sectors proved to be insignificant. The consumer cyclicals sector index is the only sector that has a negative impact on market performance. Meanwhile, the energy and transportation sectors have no significant effect on market returns. Meanwhile, the financial sector is the dominant sector that has a positive influence on market performance